2022
DOI: 10.1101/2022.12.20.22283750
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Monkeypox Post COVID19: Knowledge, Worrying, and Vaccine Adoption of the Arabic General Population

Abstract: Background: The outbreak of monkeypox was designated a global public health emergency by the World Health Organization on July 23, 2022. There have been more reported 60000 cases worldwide, most of which are in places where monkeypox has never been seen due to the travel of people who have the virus. This research aims to evaluate the Arabic general population on monkeypox disease, fears, and vaccine adoption after the WHO proclaimed a monkeypox epidemic and to compare these attitudes to those of the COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have suggeste decision-making process across a multitude of vaccines for both children and adults (Zingg and Siegrist, 2012;Swed, S. et al 2023). A recent study highlighted the stark disparity in COVID-19 knowledge and attitudes among racial/ethnic groups in the United States.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggeste decision-making process across a multitude of vaccines for both children and adults (Zingg and Siegrist, 2012;Swed, S. et al 2023). A recent study highlighted the stark disparity in COVID-19 knowledge and attitudes among racial/ethnic groups in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that “knowledge” may form “an important factor shaping” decisions about vaccinations; misinformation about vaccines and any impending “consequences of vaccinations” can affect the decision‐making process across a multitude of vaccines for both children and adults (Zingg and Siegrist, 2012; Swed, S. et al 2023). A recent study highlighted the stark disparity in COVID‐19 knowledge and attitudes among racial/ethnic groups in the United States.…”
Section: Introductionmentioning
confidence: 99%